An estimation of the population incidence of adult unilateral vocal fold mobility impairment in England. (July 2015) - Nouraei, S. A. Reza; Middleton, Steve E.; Butler, Colin R.; Sandhu, Guri S.
Abstract: We estimate the population incidence of adult unilateral vocal fold mobility impairment at 5.13 per 100, 000 per year.